Pengaruh Media Audio Visual terhadap Prestasi Belajar Siswa di Madrasah Ibtidaiyah Nurul Ilmi Citeureup Bogor - Agus Suryana; Indra Noviansyah; Farah Tamara (EduInovasi: Journal of Basic Educational Studies, 2022)
This study aims to examine the effect of visual learning media on science learning outcomes for fifth grade students at MI Nurul Falah Citeureup. This research method uses a pre-experimental design. The research sample was 20 students consisting of 13 male students and 7 female students. The data collection technique used pre and post test with t test analysis. The results showed that the application of visual learning media in science subjects could improve student learning outcomes. This is indicated by the average IPA pretest score of 62, while the posttest average score of 83.25. Likewise, the calculation results obtained by t count of 7.04 > t table 2.10, thus t count > t table, it can be concluded that there is a significant influence of visual learning media on science learning outcomes. Keywords: visual learning media, learning achievement, natural science